2014
DOI: 10.1016/j.bone.2013.12.025
|View full text |Cite
|
Sign up to set email alerts
|

Parathyroid hormone receptor mediates the anti-myeloma effect of proteasome inhibitors

Abstract: Clinically significant serum parathyroid hormone (PTH) variations have been reported in multiple myeloma (MM) patients treated with proteasome inhibitors. To elucidate the association between serum PTH variations and proteasome inhibition in MM, the effect of PTH and PTHR1 ligands on the proteasome inhibitors bortezomib and carfilzomib in vitro and in vivo was determined. The MM cell lines ARP1, OC1 and 5TGM1 expressed mRNA and protein encoding PTH receptor 1 (PTHR1). Treatment of 5TGM1 cells with either PTH(1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…Our data showed that the positive effect of BOR on DEX‐induced osteocyte death was enhanced when combined with a PTH(1‐34) short‐term treatment compared with treatment with BOR and PTH(1‐34) alone. PTH receptor signaling has been recently reported to mediate the anti‐myeloma effect of PIs, including BOR …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our data showed that the positive effect of BOR on DEX‐induced osteocyte death was enhanced when combined with a PTH(1‐34) short‐term treatment compared with treatment with BOR and PTH(1‐34) alone. PTH receptor signaling has been recently reported to mediate the anti‐myeloma effect of PIs, including BOR …”
Section: Discussionmentioning
confidence: 99%
“…PTH receptor signaling has been recently reported to mediate the anti-myeloma effect of PIs, including BOR. (45) The mechanisms involved in MM-induced osteocyte death and the protective effect of PIs on osteocyte survival were further investigated. First, we found that autophagic death rather than apoptosis was involved in our experimental model, in either human preosteocytes or murine osteocytes, as shown by both the increased expression of the autophagy marker LC3II by Western blot and confocal microscopy and the lack of effect on caspase-3 activation and APAF-1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…This observation suggested that the anti-MM activity of bortezomib may depend on the presence of PTH and/or its receptors. Supporting this hypothesis, the anti-MM activity of bortezomib was shown to be mediated by PTHR1; concomitant treatment with a PTHR1 antagonist was found to abrogate the antitumor effect of bortezomib in a mouse model of MM [72]. Preliminary evidence also indicates that a higher expression level of PTHR1 or PTHR2 in bone marrow is associated with longer overall survival in patients with newly diagnosed MM who were enrolled in Total Therapy 3 (where bortezomib is part of the treatment regimen) [73,74].…”
Section: Proteasome Inhibitors and Bone Remodeling In MMmentioning
confidence: 99%
“…As with bortezomib, PTHR1 has been shown to mediate the anti-MM effect of carfilzomib treatment in a mouse model of MM [72]. Preclinically, carfilzomib has been shown to block PTH-induced osteoclastogenesis via inhibition of the proteasomal degradation of HDAC4 in osteoblasts and disruption of RANKL-induced NF-κB activation in osteoclasts [84].…”
Section: Proteasome Inhibitors and Bone Remodeling In MMmentioning
confidence: 99%
“…We have previously demonstrated a close interaction between the parathyroid hormone (PTH)/PTH receptor 1 (PTHR1) system and myeloma progression in vitro and in vivo [10] . Specifically, a close parallelism between rapid and transient spikes in PTH levels following proteasome inhibitor therapy and the control of myeloma progression [11] .…”
Section: Introductionmentioning
confidence: 99%